If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = loge(x + -2) Reorder the terms: 0 = eglo(-2 + x) 0 = (-2 * eglo + x * eglo) 0 = (-2eglo + eglox) Solving 0 = -2eglo + eglox Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '2eglo' to each side of the equation. 0 + 2eglo = -2eglo + 2eglo + eglox Remove the zero: 2eglo = -2eglo + 2eglo + eglox Combine like terms: -2eglo + 2eglo = 0 2eglo = 0 + eglox 2eglo = eglox Add '-1eglox' to each side of the equation. 2eglo + -1eglox = eglox + -1eglox Combine like terms: eglox + -1eglox = 0 2eglo + -1eglox = 0 Factor out the Greatest Common Factor (GCF), 'eglo'. eglo(2 + -1x) = 0Subproblem 1
Set the factor 'eglo' equal to zero and attempt to solve: Simplifying eglo = 0 Solving eglo = 0 Move all terms containing e to the left, all other terms to the right. Simplifying eglo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing e to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Add 'x' to each side of the equation. -1x + x = -2 + x Combine like terms: -1x + x = 0 0 = -2 + x Simplifying 0 = -2 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| x^(-1/2)-.5987=0 | | 6p-7=125 | | 0.3-0.82=1.13 | | 7p/5=p/120 | | 2x-38-2= | | 6x-8x+2=-22 | | 2/3x=x-3/10 | | 14=6m+18 | | -1/3-x/6=5/3 | | y=Cekt | | -6(2x+6)=-48 | | 5x^2-20x+200=0 | | 4p-100=420 | | y^2-9y=54 | | c=15+0.25s | | -84=6v | | 7/2x-2=28-x | | 125+5x=360 | | 35n+15=155 | | 35n-15=155 | | 3/y=6/y! | | 2x+2x-3= | | 16x=3.2 | | 2x+2(x-3)= | | f(-x)=1-x^2+3(-x)+8 | | -2x^2+2x-7=0 | | 12a^2+17ab-5b^2=0 | | 4cos^2x-6cosx-7=0 | | -2n+5=725 | | 8-x=-20/y | | 18=5(w+6)-8w | | -x/8≥2 |